Carte de l'Amerique et des mers voisines. (1763)
Map shows basic geography, major settlements, and territorial place names in North America, South America, West Indies, and parts of Greenland and Africa. Minimal detail shown in western portion of North America. Relief shown pictorially. No scale noted.